2013
DOI: 10.7314/apjcp.2013.14.1.359
|View full text |Cite
|
Sign up to set email alerts
|

Tax is Involved in Up-regulation of HMGB1 Expression Levels by Interaction with C/EBP

Abstract: The high mobility group box 1 (HMGB1) protein is a multifunctional cytokine-like molecule that plays an important role in the pathogenesis of tumors. In this study, real-time polymerase chain reactions and Western blot assays indicated that HMGB1 transcriptional activity and protein level are increased in Tax + -T cells (TaxP). To clarify the mechanisms, a series of HMGB1 deletion reporter plasmids (pHLuc1 to pHLuc6) were transfected into Tax --T cells (TaxN, Jurkat) and Tax + -T cells (TaxP). We found that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…In addition, Tax increased HMGB1 secretion in T cells. These results are consistent with those reported previously (11). Tax expression did not correlate with the upregulation of HMGB1 mRNA in HTLV-I-infected T-cell lines.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In addition, Tax increased HMGB1 secretion in T cells. These results are consistent with those reported previously (11). Tax expression did not correlate with the upregulation of HMGB1 mRNA in HTLV-I-infected T-cell lines.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, it plays an important role in cellular transformation (3,4). Recently, it has been reported that Tax is involved in upregulation of HMGB1 expression by interaction with CCAAT/enhancer binding protein (11). The present study found that HMGB1 mRNA was abundantly expressed in HTLV-I-infected T-cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results represent the means ±SD of triplicate determinations. One-way ANOVA; *, P < 0.05; **, P < 0.01. sequencing results confirmed that the PCR products corresponded to HMGB1 promoter sequence ( Figure 5E) [41].…”
Section: Pedv-n Is Enriched In the Hmgb1 Promotor And C/ebp Binding Msupporting
confidence: 55%
“…Tax acts as a transcriptional activator by associating with specific DNA-bound protein and transcript factors. A recent study indicated that Tax can interact with C/EBPs in HMGB1 promoter and promote subsequent HMGB1 expression in CD4+ T-cells (Zhang et al, 2013b). These findings suggest that HMGB1 may be involved in HTLV-1-mediated adult T-cell leukemia.…”
Section: Hmgb1 Transcriptional Regulation (Figure 8)mentioning
confidence: 99%